Astronomy in Ukraine: Overview of the situation and strategic planning for 2004-2011 - Yatskiv, Ya.S.; Vavilova, I.V. (Кинематика и физика небесных тел, 2003)
This paper was also discussed at Ihe EAS General Meeting in Budapest (August, 2003), at the III All-Ukrainian Conference on Perspective Space Research in Katsiveli (September, 2003), at the NATO Advanced Study Institute in Yalta (September, 2003).
The authors are gratefull to Prof. I. Andronov, Prof. V. Karetnikov, Prof. M. Steshenko, Dr. O. Shulga, Dr. B. Novosyadly, and Dr. T. Kostiuk for their comments and suggestions. Vavilova I. B. thanks the STCU for the grant to visit JENAM-2003 in Budapest and to present this paper at the EAS General Meeting.